The Coherence of Naturalistic Personal Pantheism - Lancaster-Thomas, Asha (2020)
This paper examines the coherence of naturalistic personal pantheism (NPP) in an attempt to reconcile pantheism, naturalism, and a personal concept of God. NPP proposes that i) God is identical with the universe, ii) the universe is entirely natural, and iii) God is personal. Several critics of accounts of a God such as this have voiced concerns about a natural?—?as opposed to a supernatural?—?God, since a natural God cannot be worship-worthy. In response, I propose a controversial premise?—?physical primacy?—?to justify the worship-worthiness of a natural God. Physical primacy maintains that physical existence is a great-making property, therefore a God that exists naturally is greater than a God that exists supernaturally. I maintain that NPP is an attractive alternative to other theisms because it bypasses the pairing problem, presents a worship-worthy concept of God, and boasts ontological simplicity.
Keywords: God; Naturalism; Pantheism; Personhood